The outbreak of the new coronavirus infection in pediatric TB department - M. F. Gubkina; I. Yu. Petrakova; N. V. Yukhimenko; S. S. Sterlikova; Yu. Yu. Khokhlova; R. B. Аmansakhedov (Туберкулез и болезни лёгких)
The objective: to analyze the course of the new coronavirus infection (COVID-19) in children with active respiratory tuberculosis. Subjects and methods. The article describes results of retrospective analysis of the course of the new coronavirus infection in 25 children (3-12 years old) with active respiratory tuberculosis during the outbreak of COVID-19 in an in-patient TB unit.Results. 24 (96%) persons got infected after the close exposure to the coronavirus infection, and 1 (4%) child didn't get infected. The diagnosis was verified by polymerase chain reaction (detection of RNK of SARS-CoV-2) in 33.3%, by enzyme immunoassay (detection of IgG antibodies to SARS-CoV-2 in 1 month after quarantine removal) in 100%. 58.3% of children with respiratory tuberculosis (14 people) infected with coronavirus infection had minimal respiratory symptoms, that did not differ from signs of other respiratory viral infections; clinical manifestations of the disease were completely absent in 41.7% (10) patients. Coronavirus pneumonia was diagnosed in 4 (16.7%) children who suffered from COVID-19, they had no clinical signs of lower respiratory tract disorders and no body temperature increase; 3 patients had no signs of respiratory viral infection; in all cases, the lung damage detected by computed tomography didn't exceed 10%. In 2 months after the removal of quarantine, no IgG antibodies to SARS-CoV-2 were detected in 2 out of 10 examined children (20.0%), thus there was a chance for re-infection. No mutual aggravating effect of coronavirus infection and tuberculosis was revealed in their combination over the entire observation period (4 months).